Clinical Studies on the Treatment of Novel Coronavirus Pneumonia With Traditional Chinese Medicine—A Literature Analysis - Zhou, Zhihuan; Gao, Ning; Wang, Yumeng; Chang, Pengcheng; Tong, Yi; Fu, Shufei (Frontiers in Pharmacology, 2020)
Objective: This study aims to analyse the current situation and characteristics of traditional Chinese medicine for treatment of novel coronavirus pneumonia, clarify its clinical advantages and provide a reference for clinical treatment. Methods: Clinical randomised controlled trials, clinical control trials and case series research involving the use of Chinese medicine for novel coronavirus pneumonia treatment were selected from PubMed, Chinese Journal Service Platform of CNKI, VIP and WanFang Data Knowledge Service Platform from the establishment of the library to 11:00 on April 15, 2020. The published information, research design, intervention measures and research observation index were statistically analysed. Results: Twenty studies were included. The research methods were mainly clinical controlled trials. The observation indicators were mostly fever improvement time, cough improvement time, shortness of breath improvement time, chest CT and CRP examination. Maxing Ganshi（Ephedrae Herba, Armeniacae Semen Amarum, Glycyrrhizae Radix Et Rhizoma, and Gypsum Fibrosum） decoction was the core prescription. The most frequently used drugs were Glycyrrhizae Radix Et Rhizoma(Gancao), Ephedrae Herba(Mahuang), Armeniacae Semen Amarum(Kuxingren), Atractylodis Rhizoma(Cangzhu), and Scutellariae Radix (Huangqin). The most frequently used drug combination was Ephedrae Herba(Mahuang)–Armeniacae Semen Amarum(Kuxingren). The most frequently used Chinese patent medicine was Lianhua Qingwen capsule/graunle. Conclusions: Traditional Chinese medicine has widely used for novel coronavirus pneumonia in China. It is worthy of global attention. Also, high-quality randomized controlled clinical trials on the effectiveness and safety of traditional Chinese medicine in the treatment of novel coronavirus pneumonia need to carry out.